2021
DOI: 10.1007/s10620-021-07292-9
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Cold Snare Polypectomy Can Be Performed for Recurrent Benign Lesions After Cold Snare Polypectomy

Abstract: Background and Aims Recurrence after cold snare polypectomy (CSP) sometimes occurs. We assessed the feasibility of repeat CSP for recurrence after CSP. Methods We retrospectively reviewed recurrent lesions after CSP which were resected by repeat CSP from 2016 to 2021 in our institution and analyzed clinical outcomes of repeat CSP, comparing those of non-recurrent 454 lesions receiving standard CSP in 2016 and follow-up colonoscopy. We also analyzed the recurrent rate among cases receiving follow-up in both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Definitive treatment options for recurrent lesions after CSP remain debatable. Yoshida et al 68 showed that repeated CSP was safe and effective in 80 patients with recurrent lesions after prior CSP for benign tumors. However, no large-scale study has been conducted on how to manage cases of local recurrence due to cancer remnants after CSP; therefore, future prospective studies are warranted.…”
Section: Risk Of Recurrence After Csp and Treatment After Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Definitive treatment options for recurrent lesions after CSP remain debatable. Yoshida et al 68 showed that repeated CSP was safe and effective in 80 patients with recurrent lesions after prior CSP for benign tumors. However, no large-scale study has been conducted on how to manage cases of local recurrence due to cancer remnants after CSP; therefore, future prospective studies are warranted.…”
Section: Risk Of Recurrence After Csp and Treatment After Recurrencementioning
confidence: 99%
“…Definitive treatment options for recurrent lesions after CSP remain debatable. Yoshida et al 68 . showed that repeated CSP was safe and effective in 80 patients with recurrent lesions after prior CSP for benign tumors.…”
Section: Risk Of Recurrence After Csp and Treatment After Recurrencementioning
confidence: 99%